2007
DOI: 10.1002/mnfr.200600302
|View full text |Cite
|
Sign up to set email alerts
|

Is garlic a promising food for benign prostatic hyperplasia and prostate cancer?

Abstract: Prostate cancer is one of the most common male malignancies worldwide, and benign prostatic hyperplasia (BPH) is a common cause of lower urinary tract symptoms in elderly men. Garlic (Allium sativum) has been known to have anti-inflammatory, anti-cancer and antioxidant effects. Owing to these effects, garlic and its preparations have been used for the treatment of prostate cancer and relief of BPH symptoms for decades. It is thought that the mechanism(s) through which garlic may show anti-cancer and anti-infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…During last two decades, it was shown that garlic is endowed with antibiotic, antifungal [21] and antibacterial activities [22]. Current observations have substantiated that garlic may also be used against antiartherosclerosis, hypolipidemic [2324] and anticarcinogenesis activities [25–26]. Moreover, several studies have shown garlic to be a potent immunomodulator.…”
Section: Introductionmentioning
confidence: 99%
“…During last two decades, it was shown that garlic is endowed with antibiotic, antifungal [21] and antibacterial activities [22]. Current observations have substantiated that garlic may also be used against antiartherosclerosis, hypolipidemic [2324] and anticarcinogenesis activities [25–26]. Moreover, several studies have shown garlic to be a potent immunomodulator.…”
Section: Introductionmentioning
confidence: 99%
“…inhibition of platelet aggregation and vasodilatation (Agarwal 1996), that might also contribute to the antimetastatic activity (and cardiovascular effects) described for several garlic compounds (Ariga and Seki 2006;Hassan 2004;Devrim and Durak 2007;Howard et al 2007). Apart from the fact that diverse OSCs interact with different CYP450s, this effect is additionally dependent on the model, the dose and the scheme of application (Agarwal 1996;Herman-Antosiewicz and Singh 2004;Davenport and Wargovich 2005).…”
Section: Overview Of Molecular Targets Affected By Oscsmentioning
confidence: 95%
“…Sweden, Italy, USA, Japan) all reporting a reduced risk of stomach, esophageal and colorectal cancers (Shukla 2007). Less often garlic's efficacy against other tumors, such as prostate cancer or benign prostatic hyperplasia (BPH), cancers of head, neck, breast, skin or lung, were elucidated (Devrim and Durak 2007;Fleischauer and Arab 2001;Garlic and 2008;Tilli et al 2003;Hsing et al 2002;Challier et al 1998), suggesting that effects are not restricted to topical applications, but also occur systemically. For example population based diet studies in England revealed a decreased risk of prostate cancer in elderly men caused by a high total fat intake when consuming garlic.…”
Section: Epidemiological Studies and Recordsmentioning
confidence: 96%
See 2 more Smart Citations